ANALISIS BIBLIOMETRIK DENGAN VOSVIEWER TERHADAP PERKEMBANGAN PENELITIAN AUDIT PEMASARAN - Ine Hanisa Pratama; Safnah Safnah; Salsabilla Ronardi; Ulviana Agustina; Siti Rodiah (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The subject of marketing audits has been the center of interest for both academic and professional researchers. The existence of marketing audits can help improve corporate governance, prevent fraud and increase the efficiency of company operations. The purpose of this study is to determine the development of marketing audit research using bibliometric analysis in the VOSviewer 1.6.20 application, and research data is facilitated through the use of the Publish or Perish (PoP) application. The data collected was obtained from examining search results related to the keyword “Marketing Audit” obtained from scientific journals indexed by Google Scholar as many as 1,870 articles, covering the period 2005 to 2024, have been identified in this study. The research method used in this study is qualitative. The research shows that the development of marketing audit research from the period 2005 to 2024 experienced an up and down graph, with the most publications in the period 2023 and the smallest in 2019. The results show the importance of bibliometric analysis in providing analytical data about this study providing guidance and serving as a valuable resource for researchers involved in the exploration and identification in this research theme